Training and Technical Assistance to Enhance Capacity Building Between Prevention Research Centers and Their Partners - Antonia J. Spadaro, EdD, RN; Jo Anne Grunbaum, EdD; Nicola U. Dawkins, PhD, MPH; Demia S. Wright, MPH; Stephanie K. Rubel, MPH; Diane C. Green, PhD, MPH; Eduardo J. Simoes, MD, MPH (Centers for Disease Control and Prevention, 2011)
IntroductionThe Centers for Disease Control and Prevention has administered the Prevention Research Centers Program since 1986. We quantified the number and reach of training programs across all centers, determined whether the centers' outcomes varied by characteristics of the academic institution, and explored potential benefits of training and technical assistance for academic researchers and community partners. We characterized how these activities enhanced capacity building within Prevention Research Centers and the community.MethodsThe program office collected quantitative information on training across all 33 centers via its Internet-based system from April through December 2007. Qualitative data were collected from April through May 2007. We selected 9 centers each for 2 separate, semistructured, telephone interviews, 1 on training and 1 on technical assistance.ResultsAcross 24 centers, 4,777 people were trained in 99 training programs in fiscal year 2007 (October 1, 2006-September 30, 2007). Nearly 30% of people trained were community members or agency representatives. Training and technical assistance activities provided opportunities to enhance community partners' capacity in areas such as conducting needs assessments and writing grants and to improve the centers' capacity for cultural competency.ConclusionBoth qualitative and quantitative data demonstrated that training and technical assistance activities can foster capacity building and provide a reciprocal venue to support researchers' and the community's research interests. Future evaluation could assess community and public health partners' perception of centers' training programs and technical assistance.